Stages of Population Ageing: Evidence from Nepal - Poudel, Bhumidatta (Journal of Kapan Multiple Campus, 2025)
This paper highlights that the demographic transition of population aging is a significant topic in population studies, referring to the shift in the age distribution of a population towards older age groups, often accompanying broader demographic transitions characterized by declining fertility and mortality rates. In light of the discussion, panel data (1950-1923) on Nepal demonstrated that fertility, mortality, and population growth rates have been declining gradually, suggesting that the demographic transition of ageing is critical for fostering sustainable development and improving the quality of life for older adults at later stages. The latest national population and housing census 2021 is also supporting this social construction of ageing in Nepal.